2021
DOI: 10.1108/bfj-08-2020-0748
|View full text |Cite
|
Sign up to set email alerts
|

Extending the memorable tourism experience model: a study of coffee tourism in Vietnam

Abstract: PurposeDespite the increasing recognition of coffee tourism, there is limited research on the influence of memorable tourism experiences (MTEs) on coffee tourist behaviours. This investigation attempted to fill the gap in extending the MTE model by integrating travel motivations and expectation–confirmation theory (ECT).Design/methodology/approachA mixed-method approach was employed. A survey questionnaire containing closed- and open-ended questions was used to obtain quantitative and qualitative information. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 46 publications
1
28
0
2
Order By: Relevance
“…Furthermore, as per the ECT, wherein the “confirmation of expectation” plays a key role in the prediction of future behavior (Chen et al , 2021), we posit (Figure 1) that increased SR – which can also be considered akin to confirmation of expectations (or positive disconfirmation) – shall enhance MTE, which, in turn, shall positively enhance revisit intention and recommend intention. This has led to the integration of the self-enhancement model and ECT in this study.…”
Section: Review Of Literaturementioning
confidence: 86%
“…Furthermore, as per the ECT, wherein the “confirmation of expectation” plays a key role in the prediction of future behavior (Chen et al , 2021), we posit (Figure 1) that increased SR – which can also be considered akin to confirmation of expectations (or positive disconfirmation) – shall enhance MTE, which, in turn, shall positively enhance revisit intention and recommend intention. This has led to the integration of the self-enhancement model and ECT in this study.…”
Section: Review Of Literaturementioning
confidence: 86%
“…Cotter et al (2021) determined that visitors' intentions to provide a positive recommendation correlated with visit satisfaction via pre-and post-visit surveys at an art museum [47]. Chen et al (2021) confirmed that coffee tourists' behavioral intentions are strongly influenced by satisfaction [48].…”
Section: Theoretical Framework 221 Satisfaction-behavioral Intentionsmentioning
confidence: 99%
“…In addition, MTEs also show a significant effect on overall satisfaction (Prayag and Ryan, 2012;Kim, 2018;Wong et al, 2019). More specifically, Chen et al (2021) found that an MTE on coffee tourism strongly reinforced tourists' satisfaction. Stavrianea and Kamenidou (2021) revealed that the formation of tourists' satisfaction is greatly related to positive MTEs.…”
Section: Destination Image Place Attachment and Overall Satisfactionmentioning
confidence: 98%
“…Referring to previous tourism studies, it is indicated that one destination providing tourists with MTEs can make tourists more satisfied (Chen et al, 2021), enhance their place attachment (Tsai, 2016), and increase their repeat behavior (Wong and Lai, 2021). This study embarks on an alternative way to test tourists' behavioral intention of visiting other similar tourism destinations.…”
Section: Introductionmentioning
confidence: 94%